Malaysia Stroke Council guide on acute stroke care service during COVID-19 pandemic - Wan Zaidi, Wan Asyraf; Yusof Khan, Abdul Hanif Khan; Law, Wan Chung; Hoo, Fan Kee; Looi, Irene; Ang, Chong Lip; Wong, Yee Choon; Mak, Choon Soon; Tan, Wee Yong; Wan Yahya, Wan Nur Nafisah; Basri, Hamidon (Malaysian Medical Association, 2020)
On the 18th of March 2020, the Malaysia government declared a movement control order (MCO) due to the unprecedented COVID-19 pandemic. Although the majority of patients presented with respiratory-related symptoms, COVID-19 patients may present atypically with neurological manifestations and may even have an increased risk of stroke. The Malaysia Stroke Council is concerned regarding the level of care given to stroke patients during this pandemic. During the recent National Stroke Workflow Steering Committee meeting, a guide was made based on the currently available evidences to assist Malaysian physicians providing acute stroke care in the hospital setting in order to provide the best stroke care while maintaining their own safety. The guide comprises of prehospital stroke awareness, hyperacute stroke care, stroke care unit and intensive care unit admission, post-stroke rehabilitation and secondary prevention practice. We urge continuous initiative to provide the best stroke care possible and ensure adequate safety for both patients and the stroke care team.